Washed up: the end of an era for adrenal incidentaloma CT - James H. Seow; Damien L. Stella; Christopher J. Welman; Arjuna J. Somasundaram; Jan F. Gerstenmaier (Insights into Imaging, 2025)
Abstract For over 20 years, the two key tenets of adrenal incidentaloma (AI) evaluation have been the upper threshold of 10 Hounsfield units (HU) on noncontrast CT (ncCT) to delineate benignity, and the utilisation of adrenal washout CT (AWCT) to evaluate those above this cutoff. In light of growing recent evidence that challenges these two traditional principles, as well as re-evaluation of the data that led to their acceptance, we conclude that neither of these mainstays of adrenal CT remains relevant in modern AI diagnostic workup. With an appropriate definition of an incidentaloma and endocrine assessment for the majority of adrenal lesions, our analysis establishes that the use of AWCT should be ceased in the assessment of AIs, and that a 20 HU attenuation threshold for lesions < 4 cm should replace the traditional 10 HU threshold to exclude malignancy in this patient population. We therefore propose new recommendations for the management of AIs based primarily on CT attenuation and lesion size on ncCT. Critical relevance statement Increasing the CT attenuation threshold to 20 HU for lesions < 4 cm and eliminating washout CT for true adrenal incidentalomas, together with recommendations for endocrine assessment, will significantly decrease the over-investigation of overwhelmingly benign adrenal lesions, whilst confidently excluding malignancy. Key Points True incidentalomas exclude current or prior extra-adrenal malignancy and clinically suspected adrenal disease. Adrenal washout CT was never proven in the malignancy-sparse true incidentaloma population. Hormonal correlation in parallel with < 20 HU and < 4  cm thresholds of homogeneous lesions on noncontrast CT excludes malignancy. Graphical Abstract